2019
DOI: 10.3390/biom9040129
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 as a Predictor of Coronary Atherosclerotic Plaque Instability in Stable Coronary Heart Disease Patients with Elevated Lipoprotein(a) Levels

Abstract: We sought to investigate whether levels of matrix metalloproteinases (MMPs) and their inhibitors predict coronary atherosclerotic plaque instability, as assessed by intravascular ultrasound (IVUS) virtual histology during coronary angiography. Blood samples were collected before angiography in 32 subjects (mean age 56 ± 8 years) with stable coronary heart disease (CHD) and elevated lipoprotein(a) (Lp(a), 94 ± 35 mg/dL). Levels of high-sensitivity C-reactive protein (hsCRP), apolipoprotein B100 (apoB100), MMP-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 31 publications
2
25
0
2
Order By: Relevance
“…Inflammatory cells can release large amounts of MMP-9 into plaque tissue, which can then degrade the ECM, resulting in a thin fibrous cap and plaque instability. Numerous studies have demonstrated that MMP-9 levels are higher in vulnerable plaques than in stable plaques, and high circulating levels of MMP-9 are closely related to adverse cardiovascular and cerebrovascular events [ 48 , 53 , 62 , 141 143 ]. Depletion of the MMP-9 gene or inhibition of MMP-9 expression or activity can significantly prevent plaque instability.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells can release large amounts of MMP-9 into plaque tissue, which can then degrade the ECM, resulting in a thin fibrous cap and plaque instability. Numerous studies have demonstrated that MMP-9 levels are higher in vulnerable plaques than in stable plaques, and high circulating levels of MMP-9 are closely related to adverse cardiovascular and cerebrovascular events [ 48 , 53 , 62 , 141 143 ]. Depletion of the MMP-9 gene or inhibition of MMP-9 expression or activity can significantly prevent plaque instability.…”
Section: Discussionmentioning
confidence: 99%
“…In the early phase of myocardial infarction, MMP‑9 release is stimulated, as it cleaves mediators derived from neutrophils and dying cardiomyocytes [ 21 ]. The MMP‑9 plasma levels are elevated in coronary heart disease [ 26 , 27 ] and associated with atherosclerotic plaque destabilization [ 28 , 29 ], acute coronary events [ 30 , 31 ] and mortality [ 32 ] in these patients. Accordingly, MMP‑9 was shown to be up-regulated during heart failure [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is also the most upregulated gene following the Listeria infection in zebrafish, and can be used a protective molecule [12]. Besides, MMP-9 is a strong, independent predictor of atherosclerotic plaque instability [45]. The results suggest that NtMMP-9 (aNtMMP-9) may have a basic function to regulate inflammatory and immune responses of tilapia against a S. agalactiae infection.…”
Section: Heterologous Expression and The Enzyme Activity Of Ntmmp-9mentioning
confidence: 92%